Biomass gasification and pyrolysis : practical design and theory - Basu, Prabir, 1946- (Amsterdam : Elsevier, 2010)
Modernized biomass gasification for power generation has attracted increasing interests as an attempt to reduce our reliance on fossil fuel. In fact, over the past couple of years, a lot of RD&D has gone into overcoming the technical hurdles of biomass gasification mainly producing clean gas which is free of particulates and tars bed agglomeration and biomass feeding/handling. Biomass Gasification Design Handbook offers engineers and scientist a ?hands on? reference for understanding and successfully overcoming these hurdles. In this book, readers find a versatile resource that not only explains the basic principles of energy conversion and biomass conversion systems but also provides valuable insight into the design of biomass gasifiers. Thorough in his coverage, the author provides many worked out design problems, step-by-step design procedures, and real data on commercially operating systems. In addition, the book contains four valuable appendices that eliminate the need to search for essential information. Includes step-by-step design procedures and case studies for Biomass Gasification Provides worked process flow diagrams for gasifier design. Covers integration with other technologies (e.g. gas turbine, engine, fuel cells)